Computer Simulation Model for the study of the Food Chain (Research, Society and Development, 2022)
This work presents the application of a computer simulation model to minimize the teachers, difficulties in showing the natural actions that occur in the food chain that hinder the teaching and learning process. The use of computer simulation models in the teaching of Ecology for elementary education proves to be an innovative tool, promoting the approximation between students and their object of knowledge. The objective was to create a teaching strategy using virtual scenarios in order to stimulate the ability to build concepts of the food chain theme. To describe the dynamics of biological systems, a computer simulation program was developed based on the prey-predador model of Lotka-Volterra. Data collection was performed qualitatively through the analysis of responses from experiments and virtual situations. The pedagogical approach is developed based on Jean Piaget’s constructivism. From this point of view, the simulation model presents itself as an instrument to support the teaching of Ecology, helping in the leaming of new concepts. The place of study was a municipal elementary school, with 6th grade students, in the city of Manaus/Am. Based on the results obtained, it was noticed that the simulation contributes to the construction of knowledge and provides a good support for learnig.